Smart Mirror Using Rasberry Pi - et. al., Dr. M.J.Carmel Mary Belinda, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Smart mirror which is used to intimate daily actions and works which is going in home applications. In society now a days it is more useful to intimate information through laptops, desktop. By using mirror it is useful for the simple man to control it easier and faster. In these hole part of the machine works undergoes in the Raspberry pi. From these from the data which has been stored that can be used to show data what we have created like as time, data, weather condition. Smart mirror develops her personal information easier to the user. By these conditions the mirror which have implemented that should be connected to the internet and that which has been connected to the raspberry pi. From these smart mirror can easily used for day to day life from these half should act as the mirror and the another half act as the working process for users needs. Future for the better and easy to identify the going to use face recognition technique.